Prophylactic exercise-derived circulating exosomal miR-125a-5p promotes endogenous revascularization after hindlimb ischemia by targeting endothelin converting enzyme 1 - Qiu, Xueting; Zhou, Jipeng; Xu, Yanying; Liao, Longsheng; Yang, Huijun; Xiang, Yuan; Zhou, Zhengshi; Sun, Quan; Chen, Minghong; Zhang, Jiaxiong; Wu, Wanzhou; Zhu, Lingping; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Prophylactic exercise improves clinical outcomes in patients experiencing severe ischemic diseases. Previous studies have shown that exercise could alter the amount or content of circulating exosomes. However, little is known about the role of precursory exercise-derived circulating exosomes (Exe-Exo) in ischemic diseases. We therefore aimed to explore the function and mechanism of Exe-Exo in endogenous revascularization and perfusion recovery in peripheral arterial disease. Methods and Results: We first determined that 4 weeks of precursory treadmill exercise improved perfusion recovery on days 7, 14 and 21 after unilateral femoral artery ligation (FAL) but had no effect immediately after ligation. Then, local muscle delivery of Exe-Exo promotes arteriogenesis, angiogenesis and perfusion recovery, which could be abolished by GW4869, a well-recognized pharmacological agent inhibiting exosome release. This suggests that Exe-Exo mediated exercise-induced revascularization. In vitro, Exe-Exo enhanced endothelial cell proliferation, migration and tube formation. In addition, we identified miR-125a-5p as a novel exerkine through exosomal miRNA sequencing and RT-qPCR validation. Inhibition of miR-125a-5p abrogated the beneficial effects of Exe-Exo both in vivo and vitro. Mechanistically, these exercise-afforded benefits were attributed to the exosomal miR-125a-5p downregulation of ECE1 expression and the subsequent activation of the AKT/eNOS downstream signaling pathway. Specifically, skeletal muscle may be a major tissue source of exercise-induced exosomal miR-125a-5p via fluorescence in situ hybridization. Conclusions: Endogenous circulating exosomal miR-125a-5p promotes exercise-induced revascularization via targeting ECE1 and activating AKT/eNOS downstream signaling pathway. Identify exosomal miR-125a-5p as a novel exerkine, and highlight its potential therapeutic role in the prevention and treatment of peripheral arterial disease.